Local Hero sebagai Katalis Adopsi Teknologi Hijau: Tinjauan Strategi Komunikasi Lingkungan dalam Program CSR - Nabila Nuurussyifa; Diah Ajeng Purwani (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2026)
Efforts to promote green technology adoption at the community level often encounter obstacles due to gaps between organizational communication and local socio-cultural contexts, especially when CSR programs are implemented through top-down approaches. This study analyzes environmental communication strategies within the CSR program of PT Pertamina Patra Niaga AFT Adisutjipto in the Sambilegi Kidul Tourism and Education Village, focusing on the role of local heroes as catalysts for change. Guided by the Knowledge, Attitude, and Practice (KAP) model, the study examines the communication process through three stages: identification of target audiences, messages, and media; planning and development of communication media and message design; and strengthening community knowledge, attitudes, and practices. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and documentation involving the Community Development Officer (CDO), village leaders and program managers, and local heroes from assisted community groups. The object of this research is the environmental communication strategy implemented in the CSR program. The findings show that local heroes act not only as message conveyors but also as cultural mediators who adapt environmental messages and green technology practices to daily social life. Through a gradual social learning process starting at the individual level and expanding to families and the community, this strategy effectively enhances knowledge, fosters positive attitudes, and supports sustainable green technology adoption.